Utilization of Biologically Enhanced Microorganisms for the Treatment of Animal Production Wastes and Evaluation of Their Effects on Microbial Diversity and Environmental Quality of Soil and Water - Hind Faik Mahdi Alshammary,; Karim Khamis Abdullah,; Zahraa Adnan Hatm,; Noor Ali Turki, (American Journal of Biology and Natural Sciences, 2025)
Agricultural production produces organic waste, which is a threat to environmental quality and human health. Within the livestock farming sector, the production, which is likely to rise further due to increasing meat consumption, includes poultry, pig and cattle farming. Various treatment techniques are currently available, but most face limitations. Against this backdrop, biologically enhanced microorganisms (BEM)—naturally occurring native microorganisms to which additional microorganisms possessing the desired properties have been added—finely tuned to specific waste streams represent an alternative treatment strategy. Various trials demonstrated that large treatment volumes using these BEM reduced chemical oxygen demand, biological oxygen demand and ammonium concentrations, as well as eliminating antibiotics and greenhouse gases, leaching and nitrogen losses. A literature review shows how BEM can treat waste streams from poultry, porcine and bovine farmers, outlining the selection criteria, application methods and mechanisms involved, while two case studies detail the effectiveness of the BEMs used. Treatments based on BEM also impact microbial diversity in the soil and aquatic environment. Soil microbiomes shifted significantly at three sampling points, with alpha and beta diversity and function detected using amplicon sequencing and shotgun metagenomics. No similar shifts were observed for the planktonic fraction and bulk water, while microbial communities differed substantially among litter, waste and recovery samples. Planktonic networks remained unchanged in nutrient cycling, but indicators of eutrophication reduced in BEM plots. Nevertheless, treated soil maintained greater functionality and higher resilience detected through disturbance experiments. Moreover, while diversity increased metabolism and nutrient acquisition, it did not compensate for seedling establishment or microbalance restoration after tomato cultivation. These responses indicate that environmentally friendly waste treatments based on BEM support, rather than harm, the maintenance of microbial diversity in soil and water.